REBRANDING KABUPATEN SIDOARJO SEBAGAI KOTA YANG ENJOY DAN ASYIK - Firnanda P P; Werdany A P; Dessy Retha O.P; Syamsyul Ma’arif; Fatwa Nico A (Universitas Trisakti, 2021)
AbstractSidoarjo District Rebranding as Enjoyable and Fun City. Sidoarjo is a district in East Java Province, Indonesia. The capital city had a city branding namely